INTEGRASI ILMU PENGETAHUAN: Kajian Interdisipliner, Multidisipliner dan Transdisipliner Ilmu Pendidikan Islam Kontemporer - Dandi Irawan; Ramadan Syah Putra (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
The article discusses the study of the unification of knowledge in the life of the world. A scientific process that aims to find benefits for all people in a good way. This discussion discusses the verses of the Quran and Kauniyah. This is because the integration of knowledge will not be separated from these various sources. Then the background is the integration of science with the study of science dchotomies. The integration of knowledge also contains how important it is for us to seek good and correct knowledge through the learning process. The importance of seeking knowledge, must also understand the models of integration of these sciences as well as through interdisciplinary, multidisciplinary and transdisciplinary approaches.